Combined displaced fracture of the lesser humeral tuberosity and the scapular spine: A case report. (2015) - Hackl, Michael; Moro, Fabrizio; Durchholz, Holger
Highlights: Combined fractures of the scapular spine and the lesser tuberosity are rarely seen. This combination fracture leads to a high degree of instability. CT scans should be obtained for correct assessment of the fracture. ORIF can provide effective stabilization to allow early mobilization. A LCP Distal Humerus Plate fits well for reduction of the scapular spine. Abstract: Introduction Combined displaced fractures of the lesser humeral tuberosity and the scapular spine are highly uncommon and have not been previously reported in literature. Case presentation: The authors report a novel case of a 24 year-old male who sustained displaced fractures of the lesser humeral tuberosity and the scapular spine. Open reduction and internal fixation (ORIF) was performed with a LCP T-plate for the lesser tuberosity and with a LCP Distal Humerus Plate for the scapular spine. At one year, both fractures healed in anatomical alignment and the patient achieved good range of motion and a Constant score of 94 points. Discussion: While isolated fractures of the scapular spine and the lesser tuberosity can be treated conservatively, combination fractures as in the present case are highly unstable. While sufficient evidence is lacking to favor surgical treatment over conservative management, ORIF provided sufficient stability for early mobilization and led to good clinical results. Conclusion: Based on the favorable outcome of our case, we provide useful recommendations for surgeons faced with similar injuries.